Direct Assessment of the Effect of the Gly380Arg Achondroplasia Mutation on FGFR3 Dimerization Using Quantitative Imaging FRET - Placone, Jesse (Public Library of Science, 2012)
The Gly380Arg mutation in FGFR3 is the genetic cause for achondroplasia (ACH), the most common form of human dwarfism. The mutation has been proposed to increase FGFR3 dimerization, but the dimerization propensities of wild-type and mutant FGFR3 have not been compared. Here we use quantitative imaging FRET to characterize the dimerization of wild-type FGFR3 and the ACH mutant in plasma membrane-derived vesicles from HEK293T cells. We demonstrate a small, but statistically significant increase in FGFR3 dimerization due to the ACH mutation. The data are consistent with the idea that the ACH mutation causes a structural change which affects both the stability and the activity of FGFR3 dimers in the absence of ligand.